Novas tecnologias e estratégias terapêuticas no manejo da osteoartrite: uma revisão de patentes - Santos, Mariana Mendonça (2023)
Pain affects millions of individuals, contributing to the increase in morbidity, mortality and disability rates worldwide. Chronic pain is one of the main reasons why people seek medical attention, especially patients affected by osteoarthritis. Therefore, the objective of this work was to carry out a review of patents and prospecting for technological and scientific innovations for the management of osteoarthritis symptoms. The methodology consisted of searching for patent applications in the databases of the World Intellectual Property Organization and Espacenet, using the descriptors “nano*”, “arthritis or arthrosis or osteoarthritis” and/or codes A61P19/02 and A61N, selecting them through the initial reading of the title and abstract, and then the complete reading of the body of the patent. In the end, 16 patent applications were obtained related to treatments involving nanotechnology in the management of osteoarthritis and 57 patents directed to the treatment through physical agents for this pathology. The search presented the main methods using nanotechnology, through intra-articular, oral and topical routes. Considering that drugs based on nanosystems demonstrate numerous advantages compared to traditional drugs with delivery systems, due to their ability to overcome the barrier of biological and physical factors, standing out as an option in medium and long-term therapy capable of alleviate the degenerative process of osteoarthritis. Another perspective for the treatment of this pathology are non-pharmacological devices, which currently have a deficit of scientific information regarding their content, parameters used during use and mode of delivery. For the most part, these devices work through physical agents used, in general, by health professionals, mainly physiotherapists, during the rehabilitation process of the affected individual. These devices were classified according to the type of technology/therapy used, such as therapeutic electrical stimulation, phototherapy, ultrasonic therapy, electromagnetic therapy, thermotherapy and also the association between these therapies. Finally, the data obtained can help in the development of new protocols, therapeutic strategies and innovative technologies in the management of osteoarthritis symptoms, bringing light to the elucidation of this pathology, which is currently characterized as a public health problem. Therefore, the possibility of combining therapeutic approaches involving nanotechnology with the use of modern and innovative devices for the treatment of osteoarthritis presents itself as a potential alternative for the treatment and cure of this disease.